Living arrangements and mental health in Finland - Joutsenniemi, Kaisla (BMJ Group, 2006)
BACKGROUND: Non‐married persons are known to have poor mental health compared with married persons. Health differences between marital status groups may largely arise from corresponding differences in interpersonal social bonds. However, official marital status mirrors the social reality of persons to a decreasing extent, and living arrangements may be a better measure of social bonds. Little is known about mental health in different living arrangement groups. This study aims to establish the extent and determinants of mental health differences by living arrangement in terms of psychological distress (GHQ) and DSM‐IV psychiatric disorders (CIDI). METHODS: Data were used from the nationally representative cross sectional health 2000 survey, conducted in 2000–1 in Finland. Altogether 4685 participants (80%) aged 30–64 years were included in these analyses; comprehensive information was available on measures of mental health and living arrangements. Living arrangements were measured as follows: married, cohabiting, living with other(s) than a partner, and living alone. RESULTS: Compared with the married, persons living alone and those living with other(s) than a partner were approximately twice as likely to have anxiety or depressive disorders. Cohabiters did not differ from the married. In men, psychological distress was similarly associated with living arrangements. Unemployment, lack of social support, and alcohol consumption attenuated the excess psychological distress and psychiatric morbidity of persons living alone and of those living with other(s) than a partner by about 10%–50% each. CONCLUSIONS: Living arrangements are strongly associated with mental health, particularly among men. Information on living arrangements, social support, unemployment, and alcohol use may facilitate early stage recognition of poor mental health in primary health care.